Effects of Channels and Micropores in Honeycomb Scaffolds on the Reconstruction of Segmental Bone Defects - Shibahara, Keigo; Hayashi, Koichiro; Nakashima, Yasuharu; Ishikawa, Kunio (Frontiers in Bioengineering and Biotechnology, 2022)
The reconstruction of critical-sized segmental bone defects is a key challenge in orthopedics because of its intractability despite technological advancements. To overcome this challenge, scaffolds that promote rapid bone ingrowth and subsequent bone replacement are necessary. In this study, we fabricated three types of carbonate apatite honeycomb (HC) scaffolds with uniaxial channels bridging the stumps of a host bone. These HC scaffolds possessed different channel and micropore volumes. The HC scaffolds were implanted into the defects of rabbit ulnar shafts to evaluate the effects of channels and micropores on bone reconstruction. Four weeks postoperatively, the HC scaffolds with a larger channel volume promoted bone ingrowth compared to that with a larger micropore volume. In contrast, 12 weeks postoperatively, the HC scaffolds with a larger volume of the micropores rather than the channels promoted the scaffold resorption by osteoclasts and bone formation. Thus, the channels affected bone ingrowth in the early stage, and micropores affected scaffold resorption and bone formation in the middle stage. Furthermore, 12 weeks postoperatively, the HC scaffolds with large volumes of both channels and micropores formed a significantly larger amount of new bone than that attained using HC scaffolds with either large volume of channels or micropores, thereby bridging the host bone stumps. The findings of this study provide guidance for designing the pore structure of scaffolds.